The way of interaction between Vγ9Vδ2 T cells and tumor cells. (February 2023) - Zhang, Ting; Wang, Jiayu; Zhao, Anjing; Xia, Lu; Jin, Haiyan; Xia, Suhua; Shi, Tongguo
Abstract: Immunotherapy has been a promising, emerging treatment for various cancers. Gamma delta (γδ) T cells own a T cell receptor composed of γ- and δ- chain and act as crucial players in the anti-tumor immune effect. Currently, Vγ9Vδ2 T cells, the predominate γδ T cell subset in human peripheral blood, has been shown to exert multiple biological functions. In addition, a growing body of evidence notes that Vγ9Vδ2 T cells interact with tumor cells in many ways, such as TCR-mediated nonpeptidic-phosphorylated phosphoantigens (pAgs) recognization, NKG2D/NKG2D ligand (NKG2DL) pathway, Fas-FasL axis and antibody-dependent cellular cytotoxicity (ADCC) as well as exosome. More importantly, clinical studies with Vγ9Vδ2 T cells in cancers have propelled several clinical applications to investigate their safety and efficacy. Herein, this review summarized the underlying ways and mechanisms of interplay cancer cells and Vγ9Vδ2 T cells, which may help us to generate new strategies for tumor immunotherapy in the future.